Comparison of 68Ga-FAPI and 18F-FDG PET/CT in the Evaluation of Patients With Newly Diagnosed Non-Small Cell Lung Cancer - Wu, Junhao; Deng, Hao; Zhong, Haoshu; Wang, Tao; Rao, Zijuan; Wang, Yingwei; Chen, Yue; Zhang, Chunyin (Frontiers in Oncology, 2022)
Purpose: Several studies have demonstrated that 68Ga-FAPI PET/CT shows high intratumoral tracer uptake and low normal tissue uptake, allowing for excellent visualization of cancer. The purpose of this study was to compare the ability of 68Ga-FAPI and 18F-FDG PET/CT for the evaluation of newly diagnosed NSCLC. Materials and Methods: A prospective analysis of 28 individuals with histopathologically newly confirmed NSCLC that underwent 68Ga-FAPI and 18F-FDG PET/CT was conducted. The performance of two imaging modalities was compared based upon visual assessment, rates of cancer detection, and semi-quantitative parameters (target-to-background ratio [TBR], maximum standard uptake value [SUVmax]) for both primary tumors and metastases. Results: In total, this study enrolled 28 participants (13 male, 15 female; median age: 60.5 years, range: 34 – 78 years. For primary tumors, 68Ga-FAPI and 18F-FDG PET/CT have similar detection performance (28 vs. 27). However, 68Ga-FAPI PET/CT was found to more effectively evaluate most metastases as compared to 18F-FDG PET/CT. 68Ga-FAPI PET/CT detecting more metastases present within the lymph nodes (53 vs. 49), pleura (8 vs. 7), liver (4 vs. 1), and bone (41 vs. 35). The SUVmax and TBR values for 68Ga-FAPI were substantially superior to those for 18F-FDG in lymph node, pleural, and bone metastases. While the SUVmax for these two imaging approaches was comparable for hepatic metastases, 68Ga-FAPI exhibited a significantly higher TBR in relation to that of 18F-FDG. In addition, 68Ga-FAPI PET/CT demonstrates excellent N (80% [8/10]) and M (92.9% [26/28]) staging accuracy in NSCLC patients. Conclusions: 68Ga-FAPI PET/CT as an examination modality is excellent for effective evaluation of newly diagnosed NSCLC. 68Ga-FAPI PET/CT improves the detection rates of most metastases and facilitating the superior staging of patients with newly diagnosed NSCLC, relative to that achieved by 18F-FDG PET/CT.